2011
DOI: 10.1111/j.1467-9752.2011.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Habituation: A Method for Cultivating Starting Points in the Ethical Life

Abstract: The Aristotelian concept of habituation is receiving mounting and warranted interest in educational circles, but has also been subject to different lines of interpretation and critique. In this article, I bring forward Aristotle's words on habituation, and then clarify the two lines of interpretation that have developed in the contemporary philosophical literature. I argue that the mechanical interpretation contains an intellectualist bias and then argue a cognitivist view that positions habituation as the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 5 publications
0
16
0
1
Order By: Relevance
“…The Kerr effect is the birefringence produced in materials through application of a strong electric field E . John Kerr showed that Δn = ( B/λ)E 2 , where Δn = n ǁ − n ⊥ , that is, the difference in refractive indices along and perpendicular to the direction of E , λ is the wavelength of light used to measure the birefringence Δn , and B has become known as the Kerr constant.…”
Section: Introductionmentioning
confidence: 99%
“…The Kerr effect is the birefringence produced in materials through application of a strong electric field E . John Kerr showed that Δn = ( B/λ)E 2 , where Δn = n ǁ − n ⊥ , that is, the difference in refractive indices along and perpendicular to the direction of E , λ is the wavelength of light used to measure the birefringence Δn , and B has become known as the Kerr constant.…”
Section: Introductionmentioning
confidence: 99%
“…According to Aristotle, the habit, not only simplifies action and eliminates the suffering of effort, but also intensifies it (Singh et al 2015). In his view, repetition produces habits and habits produce inclination, and desire, in turn, raises action, the result of this, is a certain type of knowledge (Kerr 2011). Aristotle's phrase shows his view in this regard, saying in the essay, Nicomachean Ethics:…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In these studies, habituation is approved and they have divided this method into two categories: acceptable and unacceptable. Kerr (2011), Kristjánsson (2016), Räihä et al (2012) and Turgut (2016) are among those who have divided the method of habituation into the two types of mechanical and cognitive manners. They have sought to show that Islam has recommended the habituation method.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Steutel and Carr (1999) point out that the NE details an aretaic ethical approach, wherein there is concern over action and an evaluative idea of excellence, particularly with “the evaluation of persons, their characters, intentions and motives” (Steutel and Carr, 1999: 8). Phronesis provides insight to knowing in practical living in community that is oriented towards discerning and being responsive to what is kalon (noble and fine), thus distinguishing an evaluative capacity towards the good in relational contexts (Kerr, 2011; Vokey, 2001; Vokey and Kerr, 2011). Daniel Vokey distinguishes the kind of intrinsic goodness that Aristotle has in mind as not being relative to human interest or desire, but is good because it “embodies or actualizes what merits being valued because it is good” (Vokey, 2001: 258).…”
Section: Aristotle: An Ethics Of Knowing and Being In Practicementioning
confidence: 99%